Tax Policy and National Savings in the United States : A Survey. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1988)
This paper explores how tax policy affects the level and allocation of national savings in the United States. It argues that the effect of taxes on the overall private saving level is relatively small and uncertain and that raising public saving is the most direct and efficient way to raise national saving. However, the tax system has a powerful impact on the composition of savings and investment. The paper suggests various specific tax measures that would not only raise government revenue but also enhance the efficiency of savings and investment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet